Mass Media and Coverage of Conflict Situations in Nigeria: Implications for National Security and Integration in the Fourth Republic - Ojo, Mathew Olusola; Layefa, Goodluck; Bodunde, David Oluwafemi (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Contlict situations in post-colonial Nigeria, ranging from communal violence, indigenes/settlers crises, environmental disasters, electoral violence, political upheavals to terrorist insurgency and the attendant increasing volume of media attention they receive seem to create a sense of insecurity and disintegration within the body polity. This paper examines the role of the mass media in covering conflict situations in Nigeria within the context of the subtle elements of insecurity and social disharmony among the constituent units of the country. The paper posits that mass media coverage of contlict situations, especially in a multi-ethnic society like Nigeria should not only employ meticulous reportage that take cognizance of balance handling of all sides of the conflicts and resist explanation for violence in terms of group hatred and mutual suspicion but also avoid giving undue attention to violence, focusing rather on the domino effect of violence on political stability and democratic govemance in the body polity. The paper further posits that despite the challenges before mass media practitioners vis - a - vis govemment hostilities, poor remuneration, harassment and murder, etc., the employment of contlict-sensitive coverage is imperative for effective contlict management and peace-building in the interest of national security and integration in Nigeria’s Fourth Republic.